2019
DOI: 10.1111/jph.12851
|View full text |Cite
|
Sign up to set email alerts
|

Coconut malformation: An emerging disease caused by Fusarium proliferatum in southern Iran

Abstract: Symptoms of vegetative malformation were observed on coconut palms (Cocos nucifera L.) in the Qeshm Island, Bandar Abbas and Minab, in Hormozgan province, southern Iran. The symptoms included misshapen and dwarfed leaves with shortened, thickened and tightened leaflets in wavy and zigzag form. The aim of this study was to identify the causal pathogen of coconut palm malformation and complete Koch's postulates for putative pathogen. Small pieces of surface‐disinfested malformed vegetative tissues of coconut pal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Insect pests and diseases remain as key factors in the decline in global coconut production (Gruber et al, 2021). This has been demonstrated in the recent outbreak of coconut scale insect: Aspidiotus rigidus Reyne in the Philippines (Caoili et al, 2014); the reported newly invasive coconut rhinoceros beetle populations that threatens the Pacific Island regions (Paudel et al, 2021); the occurrence of coconut malformation caused by Fusarium proliferatum in Southern Iran (Goudarzi et al, 2019); and the association of Candidatus Phytoplasma asteris with lethal disease of coconut (Babu et al, 2020). Pest infestation and disease occurrence in coconut can be efficiently dealt with should there be a holistic integrated pest management (IPM) framework based on modern science.…”
Section: Introductionmentioning
confidence: 88%
“…Insect pests and diseases remain as key factors in the decline in global coconut production (Gruber et al, 2021). This has been demonstrated in the recent outbreak of coconut scale insect: Aspidiotus rigidus Reyne in the Philippines (Caoili et al, 2014); the reported newly invasive coconut rhinoceros beetle populations that threatens the Pacific Island regions (Paudel et al, 2021); the occurrence of coconut malformation caused by Fusarium proliferatum in Southern Iran (Goudarzi et al, 2019); and the association of Candidatus Phytoplasma asteris with lethal disease of coconut (Babu et al, 2020). Pest infestation and disease occurrence in coconut can be efficiently dealt with should there be a holistic integrated pest management (IPM) framework based on modern science.…”
Section: Introductionmentioning
confidence: 88%